THE INFLUENCE OF FINANCE KNOWLEDGE, FINANCIAL LITERACY, INDIVIDUAL EMOTIONAL INTELLIGENCE, AND PSYCHOLOGICAL BIAS FACTORS ON PERSONAL FINANCIAL MANAGEMENT - Dewi, Mertyani Sari; Nopiyani, Putu Eka; Ferayani, Made Dwi; Suryajati, I Gusti Ayu Eka; Khrisna, Gede Bagus Anjas Marga (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the effect of Financial Knowledge, Financial Literacy, Individual Emotional Intelligence and Psychological Bias Factors on Personal Financial Management. The subject of this research is the z generation in Buleleng Regency, Bali. This research is a quantitative study using multiple regression analysis techniques, classical assumption test, analysis of the coefficient of determination test, and the t-test (Partial). The results of the study show that Financial Knowledge, Financial Literacy, Individual Emotional Intelligence and Psychological Bias Factors influence Personal Financial Management in the z generation in Buleleng Regency with an adjusted R-Square value of 0.508 or 50.8%. Proving the hypothesis is done by comparison between t-table and t-count in each regression model.